The Effect of a School-Based Nutritional Program on the Anthropometric Measurements, Blood Test Results and Eating Habits of Adolescents - ERGÜN, AYŞE (MARMARA UNIV, INST HEALTH SCIENCES, 2018)
Objectives: To determine the effects of a school-based nutritional program (SBNP) designed for adolescents in high school, who are for various reasons unable to eat a midday meal, on their anthropometric measurements, blood test results and eating habits. Patients and Methods: The research used one group and was of a pretest-posttest design. 148 adolescent high school students who had difficulty accessing a midday meal and expressed willingness to participate in the study. As part of the SBNP, four sessions of nutrition education, each for one hour once a week, were held and the students were regularly provided with lunch at school for 3 months. A sociodemographic form, an Eating Habits Inventory, anthropometric measurements and blood tests. Results: Mean waist measurements were significantly lower at the last evaluation compared to the preliminary assessment. The increases in Rbc, Hb and Htc after the SBNP compared to pretest results were found to be statistically significant. Mouth sores, gingival bleeding and hair loss rates showed a significant decrease. Conclusion: The SBNP had a positive impact on increasing erythrocyte, hemoglobin and hematocrit counts and reducing waist circumference measurements. In addition, the SBNP also contributed to reducing certain skin and mucosal conditions (sores on the edges of the mouth, canker sores, gingival bleeding) and the hair loss rates that may be associated with vitamin deficiency. It is recommended that the impact of an SBNP be tested for a longer duration with a larger sample that includes a control group.
Keywords: Adolescent; hematologic tests; schools; nursing; FOOD ENVIRONMENTS; CHILDREN; LUNCH